Antara Ritual dan Pengetahuan Lokal: Strategi Mitigasi Erupsi Gunung Gamalama Perspektif Orang Ternate - Safrudin Amin; Dewi Apriani Aco; M. Guntur Cobobi (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
This research explores the disaster mitigation strategies for the eruption of Mount Gamalama from the perspective of the Ternate community. Using a qualitative ethnographic approach, it reveals how rituals and local knowledge are crucial aspects of mitigation strategy. It was found that the Ternate community integrates traditional rituals with the observation of natural signs as an early warning system. This shows a synergy between spiritual beliefs and practical knowledge in facing disaster risks. The article provides insights into the importance of maintaining local knowledge as part of an effective disaster mitigation strategy.